Characterization of β-glucosidase of Lactobacillus plantarum FSO1 and Candida pelliculosa L18 isolated from traditional fermented green olive - Yahya Rokni; Houssam Abouloifa; Reda Bellaouchi; Ismail Hasnaoui; Sara Gaamouche; Zahra Lamzira; Riadh B. E. N. Salah; Ennouamane Saalaoui; Nabil Ghabbour; Abdeslam Asehraou (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background Oleuropein, the main bitter phenolic glucoside responsible for green olive bitterness, may be degraded by the β-glucosidase enzyme to release glucose and phenolic compounds. Results Lactobacillus plantarum FSO1 and Candida pelliculosa L18 strains, isolated from natural fermented green olives, were tested for their β-glucosidase production and activity at different initial pH, NaCl concentrations, and temperature. The results showed that strains produced extracellular and induced β-glucosidase, with a molecular weight of 60 kD. The strains demonstrated their biodegradation capacity of oleuropein, associated with the accumulation of hydroxytyrosol and other phenolic compounds, resulting in antioxidant activity values significantly higher than that of ascorbic acid. The highest production value of β-glucosidase was 0.91 U/ml obtained at pH 5 and pH 6, respectively for L. plantarum FSO1 and C. pelliculosa L18. The increase of NaCl concentration, from 0 to 10% (w/v), inhibited the production of β-glucosidase for both strains. However, the β-glucosidase was activated with an increase of NaCl concentration, with a maximum activity obtained at 8% NaCl (w/v). The enzyme activity was optimal at pH 5 for both strains, while the optimum temperature was 45 °C for L. plantarum FSO1 and 35 °C for C. pelliculosa L18. Conclusions L. plantarum FSO1 and C. pelliculosa L18 strains showed their ability to produce an extracellular and induced β-glucosidase enzyme with promising traits for application in the biological processing of table olives.